FEATURES OF TEACHING MATHEMATICAL DISCIPLINES TO FUTURE SPECIALISTS IN TRANSPORT SPECIALTIES - Slavych , Viacheslav; Slavych , Anna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article examines modern approaches to teaching mathematical disciplines to students of transport specialties. The main difficulties that students face in the process of mastering mathematical knowledge are identified, and ways of adapting the educational process to the professional specifics of the transport industry are proposed. Special attention is paid to the applied nature of mathematical problems and interdisciplinary integration.